Analgesic and acute inflammation properties of the aqueous extract of dried leaves of Paullinia Pinnata (Sapindaceae) Linn - Dingom Aurelie Taylor Patience; Keugni Armand Brice; Bendegue Emebe Alexandrie Julia; Dzeufiet Djomeni Paul Désiré; Kamtchouing Pierre; Théophile Dimo (International Journal of Phytomedicine, 2017)
Inflammation is frequently associated with pain. Plants continue to be major resources for therapeutic compounds against various diseases including inflammation and pain. Paullinia Pinnata is used to treat several diseases, including rheumatism and abdominal pain. This study was undertaken to assess the analgesic and anti-inflammatory effects of Paullinia Pinnata. The analgesic activity was evaluated by using behaviour pain model in mice. The anti-inflammatory activity was carried out by using carrageenan, dextran, histamine and serotonin induced inflammation in rat. The extract was administered orally at a dose of 200 and 400 mg/kg. The results showed that the extract significantly (P< 0.001) reduced the number of writhing induced by the acid acetic. The aqueous extract reduced significantly (P< 0.001) the paw licking time in formalin model. The effect of the extract (200mg/kg) was significantly (P< 0.001) reduced in the presence of naloxone, during the inflammatory phase. In addition, the extract significantly (P< 0.05) increase latency time at all point time and all doses on nociception induced by hot plate. Concerning inflammation induced by carrageenan and dextran, the extract significantly (P< 0.001) inhibited oedema during the experimental time at the dose of 200 mg/kg. The results suggested that Paullinia pinnata aqueous extract possess analgesic activities which may interfere in both peripheral and central pathway. The anti-inflammatory activities may be mediated by either inhibiting or by blocking the release of vasoactive substances like histamine, serotonin, kinins and prostaglandins. These results justify the traditional use of the plant in the treatment of pain and inflammation.